Analisis Pengaruh Rasio CAR, NPF, BOPO, ROA dan FDR terhadap tingkat Kesehatan Bank Umum Syariah di Indonesia - Festiani, Eva Ratna (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2016)
This study aims to analyse the influence of the ratio of capital Adequacy Ratio, NPF, BOPO, ROA dan FDR againts Islamic Commercial bank soundness. This research is a quantitative study using secondary data obtained from the annual reports in Indonesian Iskamic Banks published by Bank Indonesia and the data bank health ratings obtained from annual reports of Islamic Banks and bank info research. Thus, the sample used by 11 Islamic Banks. This study use a model of ordinal Logit Regression analysis to analyze the effect of the ratio Of Capital adequacy Ratio, NPF, BOPO, ROA and FDR. The result showed that the non performing Financing (NPF) Operating Income and Operating expenses significant effect on the health of banks with significant value and NPF 0,040 0,020 Operating Expenses Operating Income, While the capital Adequacy Ratio, ROA, FDR did not have a significant influence on the health of banks, due to the significant value of each variable is more than 0.05 (p5%).